(untitled) (Revista de História Regional, 2007)
The aim of this article is to show some of the faces of the relationship between man nature in the district of Maringá revealed in the 80th decade by the local press: O Diário e O Jornal. One of these faces is the indiscriminated use of toxins, denouced by those newspapers and the other one is about the power rela-tionship thet involve the agricultural practice.